2013
DOI: 10.1186/1471-2296-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of general practitioners with the guideline-based stepped-care strategy for patients with osteoarthritis of the hip or knee: a cross-sectional study

Abstract: BackgroundTo improve the management of hip or knee osteoarthritis (OA), a multidisciplinary guideline-based stepped-care strategy (SCS) with recommendations regarding the appropriate non-surgical treatment modalities and optimal sequence for care has been developed. Implementation of this SCS in the general practice may be hampered by the negative attitude of general practitioners (GPs) towards the strategy. In order to develop a tailored implementation plan, we assessed the GPs’ views regarding specific recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…This prescription behaviour has previously been indicated in an observational study by Cardol et al [ 14 ]. Moreover, a more recent study investigating GPs’ attitudes regarding SCS recommendations, showed that 21% of the GPs (strongly) agree with the statement ‘NSAIDs should be the first choice of pain medication in patients with OA’ [ 15 ]. Given the recognized increased risk of several adverse outcomes in older adults due to the frequent use of NSAIDs and to improve guideline adherence, GPs could be advised to optimize the analgesics policy prior to consider NSAIDs prescription in patients with hip/knee OA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prescription behaviour has previously been indicated in an observational study by Cardol et al [ 14 ]. Moreover, a more recent study investigating GPs’ attitudes regarding SCS recommendations, showed that 21% of the GPs (strongly) agree with the statement ‘NSAIDs should be the first choice of pain medication in patients with OA’ [ 15 ]. Given the recognized increased risk of several adverse outcomes in older adults due to the frequent use of NSAIDs and to improve guideline adherence, GPs could be advised to optimize the analgesics policy prior to consider NSAIDs prescription in patients with hip/knee OA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPs received 2 questionnaires: a short baseline questionnaire to assess demographics and practice characteristics and a second questionnaire that was based on a cross‐sectional study of GPs' agreement with the SCS (). In this study, we collected data regarding their organization of OA care and attitudes about OA management and the SCS.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence based clinical guidelines have been published to improve clinical decision making by healthcare professionals managing lower limb osteoarthritis (Larmer, Reay, Aubert, and Kersten, 2014). Similar guidelines have been adopted and supported by GPs in the Netherlands (Smink et al, 2013), but for the GPs in this study they appear to be underutilised and to be seen to act as a brake on clinical autonomy.…”
Section: Discussionmentioning
confidence: 87%